2015
DOI: 10.1007/978-3-319-18144-8_8
|View full text |Cite
|
Sign up to set email alerts
|

H2S and Inflammation: An Overview

Abstract: Inflammation is a response to traumatic, infectious, post-ischemic, toxic, or autoimmune injury. However, uncontrolled inflammation can lead to disease, and inflammation is now believed to be responsible for several disease conditions. Research in our laboratory has shown that hydrogen sulfide (H2S) acts as a novel mediator of inflammation. At present, work in several research groups worldwide is focused on determining the role of H2S in inflammation. H2S has been implicated in different inflammatory condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…In the broader context of effects in humans, the role of H 2 S in inflammation is controversial both in vitro and in vivo . H 2 S has been shown to increase proinflammatory cytokine expression in human monocytes via the ERK–NF‐κB pathway .…”
Section: Discussionmentioning
confidence: 99%
“…In the broader context of effects in humans, the role of H 2 S in inflammation is controversial both in vitro and in vivo . H 2 S has been shown to increase proinflammatory cytokine expression in human monocytes via the ERK–NF‐κB pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Bhatia [86] reported that H 2 S acts as a novel mediator of inflammation. Soria et al [87] determined that sulphurous mineral water intake improves haematological and biochemical markers of muscle damage produced in response to endurance exercise in well-trained athletes and thus may protect from exercise-induced muscle damage.…”
Section: Cell and Immunological Messengersmentioning
confidence: 99%
“…Furthermore, sulfur donors are being attached to current drug treatments, such as naproxen, improving their anti-inflammatory effectiveness and decreasing gastrointestinal and cardiovascular side effects (13,19,35,42,105). H 2 S has beneficial effects in other organs including neurons, kidney, pancreas, and gastrointestinal and in arthritis (15,43). This suggests organ-specific delivery systems for H 2 S may need to be developed to localize therapeutic effects.…”
Section: H 2 S Mitigates Pathological Cardiac Remodeling By Inhibitinmentioning
confidence: 99%